Faith in God among "The Holly Quran" and " Kenzaa Rabbh" (Raparin Journal of Humanities (RJH), 2024)
This study deals with the uniform God in" The Holly Quran" and "Kenzaa Rabah", include introduction, four themes and Conclusion faith in God. "Kenzaa Rabah". The first theme includes the definition of the Holy Quran" and "Kenzaa Rabbh" which consider the helly book of the Sabian as it one of the oldest religions believe in the unity of Creator. The Holly Quran mentioned Sabian as they the followers of book. The second theme has been devoted to the words of faith in God in Holly Quran where inadequate from the unity of A- Huha is to create the creation. Which sent the prophets and the books ae formed by, and people join faithful and Kuffar, the happy from Paradise and naughty of the fire as the whole religion is given to Allah. It's not afraid of God. Allah doesn't see him. He is his own is the owner of creator Razak, schemer. The almighty Allah is the master in his university being not share by.The third theme adds the faith in God in "Kenzaa Rabah" and discussed the fact of accusing the Sabian that they worshiped stars and planets. Where they though ting for the existence of the learned God creator the one that doesn't hit the senser and doesn't lead to the creature.Allah is one and one religion and prophets were sent by their one God to the right and referred the words of God to the right of the whole offered by all the heavenly books.The fourth theme has been allocated to the comparison between "The Kenzaa Rabah" and "The Holly Quran" about unification of God and the presence of the relationship between the belief of Sabian and Islam.The conclusion come included the most important results of the research and including the following:The Sabian religion is regarded as the oldest heavenly religion on the face of the earth, and its history dates back to the first beginnings of unified human laws, just as the Sabian belief was discovered with the existence of the first human being: Adam, the first of the prophets, and the verses of God Almighty indicated in the horizons and in the souls, he has no partner, peer, or peer. instance. In drafting the study, the researchers used a comparative inductive technique.